2019
DOI: 10.1055/s-0039-1692699
|View full text |Cite
|
Sign up to set email alerts
|

The Petroclinoid Ligament: Its Morphometrics, Relationships, Variations, and Suggestion for New Terminology

Abstract: The anatomy and definition of the petroclinoid ligament (PCL) and its relationship with the abducens nerve are variably described. The goal of this study was to clarify the anatomy of the PCL and better elucidate its relationship with the abducens nerve. Thirty-six sides from 18 fresh-frozen adult cadaveric heads were used in this study. Specimens were all Caucasian and derived from 10 males and 8 females. The mean age at death was 79 years. Dissection of the PCL and abducens nerve was performed using a surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The petrosphenoidal ligament (also known as Grüber’s ligament, the superior sphenopetrosal ligament or the petroclival ligament) is a useful surgical landmark for the abducens nerve [ 8 , 12 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, the nomenclature for Grüber’s ligament has been inconsistent in reports in the literature, and some authors used the term petroclinoid ligament instead of the petrosphenoidal ligament [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The petrosphenoidal ligament (also known as Grüber’s ligament, the superior sphenopetrosal ligament or the petroclival ligament) is a useful surgical landmark for the abducens nerve [ 8 , 12 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, the nomenclature for Grüber’s ligament has been inconsistent in reports in the literature, and some authors used the term petroclinoid ligament instead of the petrosphenoidal ligament [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Iwanaga et al investigated the ligament’s morphology and found that Grüber’s ligament does not attach to the posterior clinoid process but to the lateral edge of the clivus. Therefore, the term petroclival ligament should be used when describing the petrosphenoidal ligament [ 26 ]. In contrast, the petroclinoid folds are folds of the dura mater that extend between the anterior and posterior clinoid processes and the petrosal part of the temporal bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fundamental structure has been named very differently at different moments of history. However, not all of the given names can fully describe its morphology adequately, and therefore, recent studies have proposed new nomenclature to clarify its anatomy [6].…”
Section: Historical Overviewmentioning
confidence: 99%
“…Interestingly, the dissection showed that the PCL's anterior attachment was primarily to the upper extension of the clivus instead of to the posterior clinoid process. Therefore, the authors concluded that its current name did not accurately describe the real anatomy of the structure and proposed the term petroclival ligament [6].…”
Section: Anatomical Description and Relationsmentioning
confidence: 99%